Nyt - Ylander, Katri; Semester, Anssi; Nousiainen, Inka; Tuunela, Arto; Hämäläinen, Ilari; Pirilä, Hannes; Salovaara, Matti; Viippola, Viljami; Sony Music Entertainment Finland (2009-) (Sony Music Entertainment (Finland), 2009)
1 kappale.